Stock exchange markets for new ventures - Carpentier, Cécile; L'Her, Jean-François; Suret, Jean-Marc (Journal of Business Venturing, 2010)
In Canada, a venture stock market lists microcap firms at a pre-revenue stage, and competes with both formal and informal venture capital (VC). This market provides a higher rate of return and seven times as many new listings to the main exchange as traditional VC. After they graduate to the main market, new listings on the main exchange succeed even if they are not venture-backed. Our results contradict the premise that because it lacks skills, tools and value-added capabilities, a public venture market is unable to compete with a private one.